2018
DOI: 10.1208/s12249-018-1060-x
|View full text |Cite
|
Sign up to set email alerts
|

Generation of a Weakly Acidic Amorphous Solid Dispersion of the Weak Base Ritonavir with Equivalent In Vitro and In Vivo Performance to Norvir Tablet

Abstract: Ritonavir is an anti-viral compound that has also been employed extensively as a CYP3A4 and P-glycoprotein (Pgp) inhibitor to boost the pharmacokinetic performance of compounds that undergo first pass metabolism. For use in combination products, there is a desire to minimize the mass contribution of the ritonavir system to reduce patient pill burden in these combination products. In this study, KinetiSol® processing was utilized to produce an amorphous solid dispersion of ritonavir at two times the drug load o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…To understand the relevance, Norvir is a marketed product that uses HME to formulate 15% ritonavir and copovidone into an ASD. 29 From the 1 H relaxation behaviors of the laboratory frame, Table 3, both the SLS-3DP and HME systems produced molecularly miscible compositions, attributed to the high agreement between ritonavir and copovidone relaxation times. 33 Previously, the importance of the formation of molecular miscible systems was shown by Hanada et al, where molecularly miscible systems exhibit greater physical stability and were found to be less prone to crystallization.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…To understand the relevance, Norvir is a marketed product that uses HME to formulate 15% ritonavir and copovidone into an ASD. 29 From the 1 H relaxation behaviors of the laboratory frame, Table 3, both the SLS-3DP and HME systems produced molecularly miscible compositions, attributed to the high agreement between ritonavir and copovidone relaxation times. 33 Previously, the importance of the formation of molecular miscible systems was shown by Hanada et al, where molecularly miscible systems exhibit greater physical stability and were found to be less prone to crystallization.…”
Section: Discussionmentioning
confidence: 98%
“…Embodying ritonavir, as the model drug within SLS-3DP, highlights the robustness of the process to formulate challenging ASDs successfully. Considering ritonavir's thermal sensitivity, 18,29 minimal exposure of the composition to the SLS laser decreases the probability of RTV degradation from excess exposure to elevated temperature. 53 The total energy absorbed by the composition is a function of the laser density and the composition's ability to absorb the wavelength emitted by the laser (Eq.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The KSD vemurafenib ASD has better dissolution and pharmacokinetic performance due to slower drug nucleation, recrystallization, and precipitation than the commercial formulation (160). Another study by Ellenberger et al demonstrated an attempt of using KSD to produce a bioequivalent ASD of ritonavir that is double the drug load of a commercially available form of ritonavir (Norvir®), in which the composition can be made into a tablet dosage form with a mass of around 45% less than Norvir® (162). The KSD produced ritonavir tablets exhibited similar performance characteristics, such as the permeation rate and in vivo pharmacokinetics, to those of Norvir®.…”
Section: Improving Upon a Commercialized Asdmentioning
confidence: 99%